Processing MIMIC-III for Evaluation of Various Blood Pressure Estimation Models - Kostoska, Magdalena; Kuzmanov, Ivan; Koteska, Bojana; Lehocki, Fedor; Madevska Bogdanova, Ana (My University, 2024)
The development of non-invasive easily available blood pres- sure estimation methods using electrocardiogram - ECG and/or photo- plethysmogram - PPG signals has gained increasing attention. However, there is a lack of consistency in the evaluation of these methods due to variations in the size and availability of data in published datasets. Our research involves retrieving, cleaning, and storing a portion of the MIMIC-III database for utilization in model training and testing. This paper outlines our methodology for processing the MIMIC-III database, along with the challenges encountered during the process.
Keywords: MIMIC-III; electrocardiogram; photoplethysmogram; blood pressure estimation; artificial neural network; deep learning